Фонетические и морфологические особенности южнобережного диалекта крымскотатарского языка - Решетов, Э.С. (Культура народов Причерноморья, 2014)
Цель статьи – ознакомить читателей с особенностями диалектов крымскотатарского
языка. В статье исследуются фонетические и морфологические особенности южнобережного
диалекта крымскотатарского языка. Анализируются гласные и согласные звуки южнобережного
диалекта. Особое внимание уделяется аффиксам настоящего и прошедшего времени, системе падежей,
причастиям, личным и указательным местоимениям. В работе представлены фонетические,
морфологические и лексические диалектизмы. Освещаются некоторые интересные факты из истории
изучения диалектов крымскотатарского языка. Мета статтi – ознайомити чiтачiв з особливостями дiалектiв кримськотатарської мови. У
статтi дослiджуються фонетичнi та морфологичнi особливостi пiвденнобережного дiалекта
кримськотатарської мови. Аналiлiзуються аффiкси теперiшнього та майбутнього часiв, система
вiдмiнкiв, дієприкметники та займенники. Представлено багато фонетичних, морфологичних та
лексичних дiалектизмiв. Присутня класифiкацiя дiалектiв. Вказуеться що майже у кожному
кримськотатарському селi були свої особливости вимови. У статтi освiтлюються деяки факт из
історії вивчення дiалектiв кримськотатарської мови. The purpose of the article is to give the reader some information on Crimean Tatar dialects. The
article deals with the most important problems which arise at practical studying dialectology. As the title implies
the article describes phonetic and morphologic structure of southern dialect of Crimean Tatar language. The
main principles of sound changes in Crimean Tatar dialects are deduced. The text gives a valuable information
on using of vowels and consonants in the work. Much attention is given to affixes of past and present tenses,
system of cases, participles, demonstrative and personal pronouns. Many phonetic, morphologic and lexical
dialecticisms are shown in the article. Different classifications of Crimean Tatar dialects are proposed. It should
be stressed that almost every village had its own linguistic peculiarities. It is described in short some interesting
facts from the history of investigation of Crimean Tatar dialects.